Therapeutic enzyme deimmunization by combinatorial T-cell epitope removal using neutral drift - Cantor, Jason R.; Yoo, Tae Hyeon; Dixit, Aakanksha; Iverson, Brent L.; Forsthuber, Thomas G.; Georgiou, George; Wells, James A. (Proceedings of the National Academy of Sciences - PNAS, 2011)
A number of heterologous enzymes have been investigated for cancer treatment and other therapeutic applications; however, immunogenicity issues have limited their clinical utility. Here, a new approach has been created for heterologous enzyme deimmunization whereby combinatorial saturation mutagenesis is coupled with a screening strategy that capitalizes on the evolutionary biology concept of neutral drift, and combined with iterative computational prediction of T-cell epitopes to achieve extensive reengineering of a protein sequence for reduced MHC-II binding propensity without affecting catalytic and pharmacological properties. Escherichia coli L-asparaginase II (EcAll), the only nonhuman enzyme approved for repeated administration, is critical in treatment of childhood acute lymphoblastic leukemia (ALL), but elicits adverse antibody responses in a significant fraction of patients. The neutral drift screening of combinatorial saturation mutagenesis libraries at a total of 12 positions was used to isolate an EcAll variant containing eight amino acid substitutions within computationally predicted T-cell epitopes—of which four were nonconservative—while still exhibiting k cat /K M = 10⁶ M⁻¹ s⁻¹ for L-Asn hydrolysis. Further, immunization of HLA-transgenic mice expressing the ALL-associated DRB1*0401 allele with the engineered variant resulted in significantly reduced T-cell responses and a 10-fold reduction in anti-EcAll IgG titers relative to the existing therapeutic. This significant reduction in the immunogenicity of EcAll may be clinically relevant for ALL treatment and illustrates the potential of employing neutral drift screens to achieve large jumps in sequence space as may be required for the deimmunization of heterologous proteins.